Recent Advances in Molecular Diagnosis of Pseudomonasaeruginosa Infection by State-of-the-Art Genotyping Techniques - Chen, Jian-Woon; Lau, Yin Yin; Krishnan, Thiba; Chan, Kok-Gan; Chang, Chien-Yi (Frontiers in Microbiology, 2018)
Pseudomonas aeruginosa is a rod-shaped Gram-negative bacterium which is notably known as a pathogen in humans, animals and plants. Infections caused by P. aeruginosa especially in hospitalized patients are often life-threatening and rapidly increasing worldwide throughout the years. Recently, multidrug-resistant P. aeruginosa has taken a toll on humans’ health due to the inefficiency of antimicrobial agents. Therefore, the rapid and advanced diagnostic techniques to accurately detect this bacterium particularly in clinical samples are indeed necessary to ensure timely and effective treatments and to prevent outbreaks. This review aims to discuss most recent of state-of-the-art molecular diagnostic techniques enabling fast and accurate detection and identification of P. aeruginosa based on well-developed genotyping techniques e.g. polymerase chain reaction (PCR), pulse-field gel electrophoresis (PFGE) and next generation sequencing (NGS). The advantages and limitations of each of the methods are also reviewed.